The role of Security Culture in The Prevention of Work Accidents Sociological Approach - Makhlouf, Boumediene; Grid, Samir (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
Security culture is an essential part of the organization's culture because it gains employees positive values, standards and trends which contributes to enhancing their security awareness and reduces professional risks to which they may be exposed as a result of their negligence or lack of compliance with occupational safety rules, so in this intervention, we will try to recognize the role of security culture in the prevention of work accidents. through a sociological approach, through which we address the concepts of security culture and employment incidents and then review the sociological approaches interpreted for a security culture, and finally conclude with the role that a security culture plays in the prevention of work accidents and the achievement of occupational safety. In general, the security culture is a feature of all human activities in the institution, as it is reflected in the behaviors and relationships of individuals, and therefore plays an active role in organizing work and human interaction, it is an inseparable element from personal relationships and the formation of order between cooperating people, and the culture of security in any organization permeates all areas of its activities and forms a bridge between its past and future, so the integration of security culture, unification and stability, reducing uncertainty, enhancing the common vision of goals and facilitating ways to solve Relationships Security problems are the key to achieving a sustainable security culture.